1991
DOI: 10.1177/00220345910700051001
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate Content in Developing Human and Bovine Enamel

Abstract: The present study describes the detailed changes in carbonate distribution throughout the different stages of development in human and bovine enamel, from early formation to maturation. Twenty-two human maxillary and mandibular deciduous anterior teeth and 46 bovine teeth were studied. The major mineral ions, calcium and phosphorus, were also analyzed to facilitate comparison of carbonate content with progressing mineralization. The results showed that as enamel matured and mineral concentration increased, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 22 publications
1
40
0
3
Order By: Relevance
“…Therefore, 68 papers were included in the final review. The studies covered seven main categories: morphology (5 studies) (22)(23)(24)(25)(26), chemical composition (11 studies) (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), physical properties (12 studies) (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), dental caries (7 studies) (6,9,(50)(51)(52)(53)(54), dental erosion/abrasion (10 studies) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64), bonding/adhesive strength (17 studies) (65)(66)(67)(68)…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, 68 papers were included in the final review. The studies covered seven main categories: morphology (5 studies) (22)(23)(24)(25)(26), chemical composition (11 studies) (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), physical properties (12 studies) (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), dental caries (7 studies) (6,9,(50)(51)(52)(53)(54), dental erosion/abrasion (10 studies) (55)(56)(57)(58)(59)(60)(61)(62)(63)(64), bonding/adhesive strength (17 studies) (65)(66)(67)(68)…”
Section: Search Resultsmentioning
confidence: 99%
“…Gwinnett et al (31) found no significant difference in fluoride uptake between etched human and bovine enamel. Sydney-Zax et al (32) showed no significant difference in carbonate content between human and bovine enamel at different stages of their development. However, the study compared primary human teeth to bovine teeth and did not clarify if primary or permanent bovine teeth were used.…”
Section: Chemical Composition Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…During maturation of enamel, the mineral content increases from initially *45 wt.% up to *98-99 wt.% (Avery 2001; Nanci 2012; Bonar et al 1991). The enamel crystal rods widen and thicken by additional growth (Rey et al 1995b;Bonar et al 1991;Smith 1998) with a simultaneous increase of the Ca/P molar ratio (Smith 1998) and a decrease in carbonate content (Sydney-Zax et al 1991;Rey et al 1991;Takagi et al 1998), finally resulting in the most highly mineralized and hardest substance produced by vertebrates. It is interesting to note that in the radular teeth of chitons, ACP was found to be the first-formed CaPO 4 mineral, which over a period of weeks was transformed to dahllite (Lowenstam and Weiner 1985).…”
Section: Teethmentioning
confidence: 99%
“…Lopes et al 6 obtiveram mais informações sobre o material alternativo para dentes humanos ao comparar esmalte e dentina humano e bovino usando dois diferentes agentes adesivos com diferentes mecanismos de ação e concluíram que o esmalte rico em carbonato é particularmente vulnerável ao ataque ácido. A concentração de carbonato no esmalte bovino é mais alta que no esmalte humano 21 . E isto, provavelmente, também ocorre na dentina, de modo que o esmalte bovino é mais poroso que o esmalte humano estando presente uma alta difusão, razão do progresso da lesão de cárie artificial.…”
Section: Discussionunclassified